I open the window and I see… “How the infant child dicovers the world that surronds him with the strengh of love” (Journal of Parents and Teachers, 2012)
A child in primary education is starting to discover the world. But because of the world that we live in nowadays, children learn to watch TV, play with videogames insteado of playing in the park. This is the reason why is important that teachers change the way of encourage students in the classroom so that they learn the basic things (affection, self-esteem) having fun at the same time.
Keywords: childhood education; esteem; affection